Phrudoneura (Diptera: Dolichopodidae) from Australia and Melanesia - Bickel, Daniel J. (Zootaxa, 2013)
The genus Phrudoneura Meuffels & Grootaert (Diptera: Dolichopodidae) from Australia, New Guinea, the Solomon Is-lands, and New Caledonia is revised, and four new species are described. Phrudoneura collessi sp. nov. occurs in tropical and subtropical Australia, and is named in honour of the Australian Dipterist, Don Colless. Phrudoneura popondetta sp. nov. is from lowland Papua New Guinea, and P. abbreviata Meuffels & Grootaert, originally described from Papua New Guinea, is now recorded from tropical Australia and the Solomon Islands. The previously described fauna of New Cale-donia of five species is reviewed and two new species are described, P. adusta and P. hibernalis. All species are keyed and illustrated. Phrudoneura is not placed in any established subfamily but is regarded as incertae sedis, perhaps having clos-est affinity with the Sympycninae.